Validation of a questionnaire to assess the level of knowledge of dentoalveolar trauma in children - Mercado-Hermoza, Adriana Elizabeth (2022)
Objective: Dentoalveolar trauma is one of the most prevalent injuries treated by the dentist and its highest incidence is in the child population, which is why the purpose of the study was to validate a questionnaire to measure the level of knowledge of dentoalveolar trauma in pediatric dentistry patients. Materials and methods: An observational, descriptive, cross-sectional and prospective research was carried out by creating an instrument composed of 21 multiple-choice questions. The instrument was subjected to an expert judgment and a pilot test to be applied to a total sample of 150 participants (50 undergraduate students of Stomatology, 50 general dentists and 50 specialists in pediatric dentistry). 50% of the sample was surveyed again (test retest). Results: the questionnaire reached a high content validity by obtaining a score of 0.98. The KR20 analysis showed a high reliability of 0.64 and the Spearman coefficient a very high reproducibility of 0.86. Conclusions: The present instrument is valid, reliable and reproducible to be executed in future investigations with the recommendations suggested in the investigation.